Sistem Informasi Geografis Pemantauan Status Gizi Balita di Kabupaten Lombok Barat untuk Pemeringkatan Daerah Rawan Gizi dengan Menggunakan Metode Analytical Hierarchy Process: Geographical Information System for Monitoring the Nutrition Status of Toddlers for Ranking Nutrition-Prone Areas Using the Analytical Hierarchy Process Method in West Lombok Regency - Sri Endang Arjarwani; qori amalia fitrasani; Ida Bagus Ketut Widiartha (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2021)
This research was triggered by the increasing number of malnutrition cases in West Lombok Regency that caused the mortality rate of children under five years old is also increasing. According to West Lombok Public Health Office, there were 49 malnutrition cases in West Lombok Regency in 2015. This number increased to 98 cases in 2016. It shows that West Lombok Public Health Office did not control and monitor these cases optimally. This research is aimed to provide the malnutrition status information and other related nutritional information, also to let the citizen send their feedbacks to the Public Health Office and Community Health Clinic. This system was built with Codeigniter framework with PHP and HTML as its programming languages. It is also integrated with the Google Maps API to show the maps of nutritional problems, health facilities, and poverties. This system was built with waterfall model as its System Development Method and Analytical Hierarchy Process (AHP) method to determine the nutritional areas. This system was tested with blackbox, whitebox and MOS. Whitebox was used to test the Analytical Hierarchy Process and the result was corresponding to the manually done calculation. Meanwhile the testing using blackbox showed that the system has been running well. The testing using MOS showed that the average assessment of public respondents to the system stated strongly agree, agree and fair were 39.04%, 55.24%, and 5.72% respectively. Keywords: Geographical Information System, Toddler’s nutritional status, Nutritional Areas, AHP